Advancing Metal‐Organic Frameworks toward Smart Sensing: Enhanced Fluorescence by a Photonic Metal‐Organic Framework for Organic Vapor Sensing. Issue 19 (12th July 2020) - Olorunyomi, Joseph F.; Sadiq, Muhammad M.; Batten, Michael; Konstas, Kristina; Chen, Dehong; Doherty, Cara M.; Caruso, Rachel A.
Abstract: Polymer‐based colloidal crystals are promising materials for the enhancement of fluorescent emissions, however, due to limited porosity, they are not yet readily deployed in chemical vapor sensing. On the contrary, metal‐organic frameworks (MOFs) are highly porous with an exceptional ability to detect a wide range of toxic chemicals through fluorescence. Here, it is shown for the first time how enhanced fluorescence of a fluorophore can be achieved by incorporating a fluorescent dye into a template‐free periodically structured MOF film. A 200‐fold fluorescent intensity amplification is observed when Nile red (NR) dye is adsorbed on zeolitic imidazolate framework‐8 (ZIF‐8) particles and is then assembled into a colloidal crystal film (NR∼ cc ZIF‐8) when compared to the disordered film (NR∼ZIF‐8). The NR∼ cc ZIF‐8 film shows a response to 100 ppm of acetone vapor at room temperature with a detection limit of 60 ppm. The NR∼ cc ZIF‐8 film shows more than 40 times higher sensitivity to toluene vapor at 770 ppm than NR adsorbed on polystyrene particles forming a colloidal crystal film. From this study, it is expected that MOFs will play a role in the future development of smart sensors for chemical and biomedical applications. Abstract : Metal‐organic frameworks are distinguished as ultrahigh porous materials with an exceptional ability to detect various toxic chemicals through fluorescence. In this study, it is shown that the photonic structure of zeolitic imidazolate framework‐8 further demonstrates the ability to intensify the fluorescence of an adsorbed fluorescent dye toward a highly sensitive and selective detection of organic vapors at room temperature.